Three days in January [compact disc, unabridged] : Dwight Eisenhower's final mission - Baier, Bret; Whitney, Catherine (HarperCollins, 2017)
Explores the presidency of Dwight D. Eisenhower through the lens of his last three days in office in January 1961, revealing him to be a model of strong yet principled leadership.